Agricultural Waste-derived Biopolymers for Sustainable Food Packaging: Challenges and Future Prospects - Thivya Selvam; Nor Mas Mira Abd Rahman; Fabrizio Olivito; Zul Ilham; Rahayu Ahmad; Wan Abd Al Qadr ImadWan-Mohtar (MDPI, 2025)
The widespread use of conventional plastic in food packaging has raised serious environmental issues due to its persistence and poor biodegradability. With growing concerns over plastic pollution and its long-term ecological impact, researchers are increasingly turning to natural, renewable sources for sustainable alternatives. Agricultural waste, often discarded in large quantities, offers a valuable resource for producing biodegradable polymers. This review discusses the environmental burden caused by traditional plastics and explores how agricultural residues such as rice husks, corn cobs, and fruit peels can be converted into eco-friendly packaging materials. Various types of biopolymers sourced from agricultural waste, including cellulose, starch, plant and animal-based proteins, polyhydroxyalkanoates (PHA), and polylactic acid (PLA), are examined for their properties, benefits, and limitations in food packaging applications. Each material presents unique characteristics in terms of biodegradability, mechanical strength, and barrier performance. While significant progress has been made, several challenges remain, including cost-effective production, material performance, and compliance with food safety regulations. Looking ahead, innovations in material processing, waste management integration, and biopolymer formulation could pave the way for widespread adoption. This review aims to provide a comprehensive overview of current developments and future directions in the use of agricultural waste for sustainable packaging solutions, comparing their biodegradability and performance to conventional plastics.